Preparation, Micromorphology and Optical Properties of SPION/Ba3V2O8: Er3+, Yb3+ Nanocomposites by Microwave-Assisted Metathetic Method - Sung Lim, Chang (Asian Journal of Chemistry, 2014)
The nanocomposites of Er3+/Yb3+ co-doped Ba3V2O8 (Ba3V2O8:Er3+/Yb3+) with superparamagnetic iron oxide nanoparticles (SPIONs) have been successfully synthesized by microwave-assisted metathetic method followed by heat-treatment. The microstructure exhibited well-defined and homogeneous morphology with the Ba3V2O8:Er3+/Yb3+ particle size of 1-3 μm and Fe3O4 particle size of 100-500 nm. The Fe3O4 nonoparticles were self-preferentially crystallized and immobilized on the surface of Ba3V2O8:Er3+/Yb3+ particles. The synthesized SPION/Ba3V2O8:Er3+/Yb3+ nanocomposites were characterized by X-ray diffraction, scanning electron microscopy and energy-dispersive X-ray spectroscopy. Other optical properties were also investigated by photoluminescence emission measurements and Raman spectroscopy.